Pandangan Islam Terhadap Subsidi - Damri Batubara (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Subsidy become a popular topic in our country. According to Indonesian government, subsidy was imposed by government all this time. That was not quite appropriate because it can also impose APBN. At the end, it can obstruct development in economic sector. The government needs to take a policy to reduce or remove subsidy slowly. The impact of reducing and removing subsidy of BBM and TDL will be rise the price of BBM followed by the rise of basic needs. That will be imposing people. Especially when the purchasing power of people is low. Meanwhile, in Islamic view the legal base of subsidy is mubah both for energy and non energy subsidy. Government have responsible to welfare people. But, government have a duty to give the subsidy of BBM and TDL or give them freely. That is why, it is important to understand subsidy in Islam view.